The Pseudorabies Virus DNA Polymerase Accessory Subunit UL42 Directs Nuclear Transport of the Holoenzyme - Wang, Yi-Ping; Du, Wen-Juan; Huang, Li-Ping; Wei, Yan-Wu; Wu, Hong-Li; Feng, Li; Liu, Chang-Ming (Frontiers in Microbiology, 2016)
Pseudorabies virus (PRV) DNA replication occurs in the nuclei of infected cells and requires the viral DNA polymerase. The PRV DNA polymerase comprises a catalytic subunit, UL30, and an accessory subunit, UL42, that confers processivity to the enzyme. Its nuclear localization is a prerequisite for its enzymatic function in the initiation of viral DNA replication. However, the mechanisms by which the PRV DNA polymerase holoenzyme enters the nucleus have not been determined. In this study, we characterized the nuclear import pathways of the PRV DNA polymerase catalytic and accessory subunits. Immunofluorescence analysis showed that UL42 localizes independently in the nucleus, whereas UL30 alone predominantly localizes in the cytoplasm. Intriguingly, the localization of UL30 was completely shifted to the nucleus when it was coexpressed with UL42, demonstrating that nuclear transport of UL30 occurs in an UL42-dependent manner. Deletion analysis and site-directed mutagenesis of the two proteins showed that UL42 contains a functional and transferable bipartite nuclear localization signal (NLS) at amino acids 354–370 and that K354, R355, and K367 are important for the NLS function, whereas UL30 has no NLS. Coimmunoprecipitation assays verified that UL42 interacts with importins α3 and α4 through its NLS. In vitro nuclear import assays demonstrated that nuclear accumulation of UL42 is a temperature- and energy-dependent process and requires both importins α and β, confirming that UL42 utilizes the importin α/β-mediated pathway for nuclear entry. In an UL42 NLS-null mutant, the UL42/UL30 heterodimer was completely confined to the cytoplasm when UL42 was coexpressed with UL30, indicating that UL30 utilizes the NLS function of UL42 for its translocation into the nucleus. Collectively, these findings suggest that UL42 contains an importin α/β-mediated bipartite NLS that transports the viral DNA polymerase holoenzyme into the nucleus in an in vitro expression system.